2012
DOI: 10.1057/kmrp.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interplay between knowledge and performance management in industrial clusters

Abstract: The concept of industrial clustering has been studied in-depth by policy makers and researchers from many fields, mainly due to the competitive advantages it may bring to regional economies. Companies often take part in collaborative initiatives with local partners while also taking advantage of knowledge spillovers to benefit from locating in a cluster. Thus, Knowledge Management (KM) and Performance Management (PM) have become relevant topics for policy makers and cluster associations when undertaking collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In our paper, we aim to test the relationship through a quantitative study, specifically devoted to SMEs, characterized by different contextual factors. Finally, there are contributions in the literature to the interplay between KM and PMSs, both at the network level [56] and single-entity level. In this latter perspective, the relevant study of Ditillo [57] focuses on knowledge-intensive firms and demonstrates the influence of knowledge complexity on management control mechanisms, in order to foster coordination and knowledge integration.…”
Section: Introductionmentioning
confidence: 99%
“…In our paper, we aim to test the relationship through a quantitative study, specifically devoted to SMEs, characterized by different contextual factors. Finally, there are contributions in the literature to the interplay between KM and PMSs, both at the network level [56] and single-entity level. In this latter perspective, the relevant study of Ditillo [57] focuses on knowledge-intensive firms and demonstrates the influence of knowledge complexity on management control mechanisms, in order to foster coordination and knowledge integration.…”
Section: Introductionmentioning
confidence: 99%
“…The effective management of knowledge-based linkages across multiple entities within the supply chain leads to the creation of new knowledge and improves supply chain's operational performance (Khalfan, Kashyap, Li, & Abbott, 2010;Marra, Ho, & Edwards, 2012;Paton & McLaughlin, 2008). Thus, KM should be acknowledged as a formal area of industrial cluster management, so that performance management practices can support knowledgeoriented initiatives and therefore make better use of the new knowledge created (Lima & Carpinetti, 2012).…”
Section: Knowledge Management In Supply Chainsmentioning
confidence: 99%
“…That is, quality knowledge can enable SMEs to be innovative and improve their performances. Although many studies have shown that knowledge management impact positively on business performance and innovation (Choi et al, 2020; Lima and Carpinetti, 2012; López-Nicolás and Meroño-Cerdán, 2011; Noruzy et al, 2013; Valdez-Juárez et al, 2016; Zaim et al, 2019), limited studies have emphasized the quality of the knowledge in question (Ganguly et al, 2019; Yoo et al, 2011). However, studies have shown that the effective use of knowledge, to a greater extent depends on its quality (Rao and Osei-Bryson, 2007).…”
Section: Introductionmentioning
confidence: 99%